2002
DOI: 10.1103/physrevlett.89.176104
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Recognition of Hydrogen-Bonded Water Networks on a Metal Surface

Abstract: The adsorption of water on Pt(111) surface has been studied with ab initio molecular dynamics simulation. Both the energetics and vibrational dynamics indicate the existence of a well-ordered molecular bilayer on this surface. This conclusion is in contrast to the recent result of water on Ru(0001) surface, but agrees with available experiments. In addition, our calculation identifies two different hydrogen bonds in the bilayer. Both can be directly recognized from the vibrational spectra of the OH stretch mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
125
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(145 citation statements)
references
References 27 publications
16
125
2
1
Order By: Relevance
“…1͑c͔͒ as well as the socalled ''reactive wetting'' leading to a dissociation of the water molecules on the surface. 20 Meng et al 19 also showed that one can identify two types of hydrogen bonds between the water molecules within a bilayer ͑66% coverage͒ adsorbed on Pt͑111͒. The simulations however could not distinguish between the two principal structures ͑OH bond pointing ''up'' or ''down''͒ due to their close adsorption energies and similar properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1͑c͔͒ as well as the socalled ''reactive wetting'' leading to a dissociation of the water molecules on the surface. 20 Meng et al 19 also showed that one can identify two types of hydrogen bonds between the water molecules within a bilayer ͑66% coverage͒ adsorbed on Pt͑111͒. The simulations however could not distinguish between the two principal structures ͑OH bond pointing ''up'' or ''down''͒ due to their close adsorption energies and similar properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, the validity of the simple model of Doering and Madey 44 was questioned based on DFT results considering structures in which the free OH bond also points towards the metal surface [19][20][21][22] ͓Fig. 1͑c͔͒ as well as the socalled ''reactive wetting'' leading to a dissociation of the water molecules on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the adsorption of water on surfaces involves a complex combination of electrostatic, van der Waals, and hydrogen bonding interactions. [21][22][23][24][25][26] Herein we report on high-resolution electron energy loss spectroscopy (HREELS) measurements on water adsorption on quasi-freestanding monolayer graphene (MLG) grown on Pt(111). HREEL experiments indicate that water molecules dosed at room temperature onto the graphene sheet can dissociate giving rise to C-H vibrational bands.…”
Section: Introductionmentioning
confidence: 99%
“…2) has become subject of investigation after Feibelman's work [18], and the theoretical [57,58] and experimental (XPS, XAS, XES) [58] evidences on the H 2 O/Pt(111) system. Adsorption energy and geometry of the "H-down" bilayer showed similarities to the "H-up" structure.…”
Section: Water Adsorption On Ru(0001)mentioning
confidence: 99%